Positive Impacts of Islamic Inabah Substance Abuse Rehabilitation Program on Health-related Quality-of-Life Profiles and Religiousness. (December 2020) - Lua, Pei Lin; Nasrulddin, Nor A. Ahmad; Mohamad, Abdul M.; Hassan, Azmi; Makhtar, Mokhairi
Abstract : Introduction: Inabah program is psychospiritual rehabilitative approach which holistically incorporates Islamic concepts and religious practices in its module encompassing of prayers, zikir, and hydrotherapy. Objectives: This study attempts to (1) determine the impact of Inabah on health-related quality of life (HRQoL) profiles and religiousness and (2) explore the relationships between HRQoL and religiousness pre- Inabah and post- Inabah . Methods: A prospective preintervention and postintervention study was conducted at 3 Inabah centers in Malaysia, recruiting new inmates aged 18 years and above who were cognitively stable and have undergone detoxification. The Malay WHOQOL-BREF (higher score=better HRQoL) and Psychological Measure of Islamic Religiousness (PMIR) (higher score=better profiles) were administered before and after Inabah intervention (minimum 2 mo). Results: One hundred fifteen all-male inmates of 144 eligible participants (79.9%) completed the program (age=30.5±7.8 y; intervention duration ⩽2.5 mo=60.9%; The Sijil Pelajaran Malaysia qualification=47.0%). Significant positive changes in Overall HRQoL, General Health, Psychological, and Islamic Obligations and Implementation issues were detected after Inabah ( P <0.05; effect size=0.27 to 0.39). Pre- Inabah, Life Satisfaction (in PMIR) correlated significantly with all HRQoL domains ( P <0.001) while Islamic Obligations and Implementation only significantly correlated with Psychological domain ( P <0.05). Majority of other PMIR versus HRQoL relationships were also significant. Post-Inabah however, dramatic increases were observed in Islamic Obligations and Implementation domain which linked significantly with all (except 1) HRQoL aspects. Conclusions: The positive impacts of the noninvasive Inabah program on HRQoL and religiousness among substance abusers were evident.